On Hilbert's Inequality for Double Series and Its Applications - Zhou Yu; Gao Mingzhe (International Journal of Mathematics and Mathematical Sciences)
This study shows that a refinement of the Hilbert inequality for double series can be established by introducing a real function u(x) and a parameter λ. In particular, some sharp results of the classical Hilbert inequality are obtained by means of a sharpening of the Cauchy inequality. As applications, some refinements of both the Fejer-Riesz inequality and Hardy inequality in Hp function are given.